Minor Antenna Proteins CP24 and CP26 Affect the Interactions between Photosystem II Subunits and the Electron Transport Rate in Grana Membranes of Arabidopsis - de Bianchi, Silvia (American Society of Plant Biologists, 2008)
We investigated the function of chlorophyll a/b binding antenna proteins Chlorophyll Protein 26 (CP26) and CP24 in light harvesting and regulation of photosynthesis by isolating Arabidopsis thaliana knockout lines that completely lacked one or both of these proteins. All three mutant lines had a decreased efficiency of energy transfer from trimeric light-harvesting complex II (LHCII) to the reaction center of photosystem II (PSII) due to the physical disconnection of LHCII from PSII and formation of PSII reaction center depleted domains in grana partitions. Photosynthesis was affected in plants lacking CP24 but not in plants lacking CP26: the former mutant had decreased electron transport rates, a lower ΔpH gradient across the grana membranes, reduced capacity for nonphotochemical quenching, and limited growth. Furthermore, the PSII particles of these plants were organized in unusual two-dimensional arrays in the grana membranes. Surprisingly, overall electron transport, nonphotochemical quenching, and growth of the double mutant were restored to wild type. Fluorescence induction kinetics and electron transport measurements at selected steps of the photosynthetic chain suggested that limitation in electron transport was due to restricted electron transport between Q(A) and Q(B), which retards plastoquinone diffusion. We conclude that CP24 absence alters PSII organization and consequently limits plastoquinone diffusion.